Bioconversion of conjugated linoleic acid by Lactobacillus plantarum CGMCC8198 supplemented with Acer truncatum bunge seeds oil - Chen, Dong-Ju (Food Sci Biotechnol, 2017)
Conjugated linoleic acid (CLA) isomers, c9, t11-CLA and t10, c12-CLA, have been proved to exhibit excellent biomedical properties for potential use in anti-cancer applications and in reducing obesity. Acer truncatum Bunge (ATB), which is rich in unsaturated fatty acids, including oleic acid, linoleic acid, and nervonic acid, is a new resource for edible oil. In the present study, we developed a new method for producing two CLA isomers from ATB-seed oil by fermentation using Lactobacillus plantarum CGMCC8198 (LP8198), a novel probiotics strain. Polymerase chain reaction results showed that there was a conserved linoleate isomerase (LIase) gene in LP8198, and its transcription could be induced by ATB-seed oil. Analyses by gas chromatography–mass spectrometry showed that the concentration of c9, t11-CLA and t10, c12-CLA in ATB-seed oil could be increased by about 9- and 2.25-fold, respectively, after being fermented by LP8198.